Data for 'Scottish Towns and Urban Society in the Enlightenment, c.1745-1820' - Harris, B; McKean, C (University of Oxford, 2016)
The dataset comprises transcripts of inventories of urban dwellers mostly from commissary court records – Registers of Testaments, Registers of Inventories and Settlements, but also several other sources, including, in the case of Dundee, a rare survival of Judicial Inventories of Minors’ Estates, records from Court of Session Sequestrations, and several chance surviving inventories from local and regional archives. Survival of this material is extremely uneven, both in respect of place and over time. Registers of inventories of settlements record house furniture and possessions on the most consistent basis, but these date only from the early nineteenth century, when clauses inserted in several acts of parliament obliged executors to lodge with the court full inventories of movable assets. Yes even then, a loophole meant that executors were not compelled to list specific items, only their total value. Registers of testaments throw up very uneven results for this kind of exercise since executors were not compelled to provide detailed breakdowns of individual items unless this was necessary to recover the estate, or where inventories were drawn up to record goods to be shared out after the death of their owner or to settle debts after bankruptcy.